2016
DOI: 10.1177/1534650116642575
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Family-Based Therapy During an Acute Medical Admission for Anorexia Nervosa

Abstract: Family-based therapy (FBT) is the evidence-based treatment of choice for anorexia nervosa (AN) in adolescents, with numerous studies providing support for its efficacy in the outpatient realm. This case report describes the application of a brief FBT intervention during an inpatient medical admission for an adolescent presenting with medical instability secondary to new onset AN. The intensive, four-session FBT-guided intervention included (a) psychoeducation and illness externalization, (b) parent skills trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Eleven additional case reports (number of total patients = 29) are described showing benefit of FBT in terms of weight gain [33,[35][36][37][38][40][41][42][43][44]. Some of these focus on twins [35,42,44], comorbid conversion disorder [43], FBT in a group home setting [38], FBT started on a medical unit [39], and FBT combined with medication [42].…”
Section: Family-based Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven additional case reports (number of total patients = 29) are described showing benefit of FBT in terms of weight gain [33,[35][36][37][38][40][41][42][43][44]. Some of these focus on twins [35,42,44], comorbid conversion disorder [43], FBT in a group home setting [38], FBT started on a medical unit [39], and FBT combined with medication [42].…”
Section: Family-based Treatmentmentioning
confidence: 99%
“…Anorexia nervosa There were three studies found examining inpatient treatment utilizing a family-based approach, one of which included 37 patients [211], and the other two studies which included one patient each (i.e. case reports) [39,63] (Table 41). Length of stay in hospital was a mean of 20.6 weeks (SD = 13.6, range 3-58) in the first study [211] and 10 days in one case report [39] and unclear in the second case report [63].…”
Section: Family-based Inpatient Carementioning
confidence: 99%
“…This approach of combining contingency management with other intervention techniques can be found in some included articles. Geller et al () combined a contingency programme with family therapy, Matthews and Peterson () treated a patient with AN with sessions of psychoeducation and meal coaching during her inpatient stay and released her with an outpatient contingency contract. Hauserman and Lavin () describe an outpatient who was on a contingency contract negotiated with the physician and received individual psychotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Bhanji and Thompson (1974) and Bhanji (1975) report about the same 11 cases and are therefore only counted once for the total number of patients. All of the included case reports and case series outline a positive short-term effect of contingency management for weight gain (Abel et al, 1987;Agras, Barlow, Chapin, Abel, & Leitenberg, 1974;Azerrad & Stafford, 1969;Bachrach, Erwin, & Mohr, 1965;Bhanji, 1975;Bhanji & Thompson, 1974;Blue, 1979;Boey, 1985;Bruch, 1974;Cinciripini, Kornblith, Turner, & Hersen, 1983;Geller, Kelly, Traxler, & Marone Jr, 1978;Hauserman & Lavin, 1977;Martin & Mclaughlin, 1975;Matthews & Peterson, 2016;Monti, Mccrady, & Barlow, 1977;Munford, 1980;Munford, Tarlow, & Gerner, 1984;Perkin & Surtees, 1976;Stumphauzer, 1969).…”
Section: Case Reports and Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation